Multimedia sebagai Inovasi dalam Pembelajaran Pendidikan Pancasila: Persepsi Siswa SMP - Pandu Rudy Widyatama (SiNORA, 2025)
The research is motivated by conventional learning methods in learning Pancasila Education in junior high schools, causing low student involvement. Along with the development of technology, multimedia is a solution to increase the effectiveness of learning. The research aims to explore students' perception of the use of multimedia in learning Pancasila Education at SMPN 16 Surabaya. The research method is qualitative with a descriptive approach. The sample consisted of 20 students in class 8B who were selected using convenience sampling. Data was collected through observation, interviews, and documentation. The results of the study show that the use of PowerPoint, learning videos, regional songs, and digital and printed LKPD increases student engagement and understanding. The Cognitive Theory of Multimedia Learning supports these findings, suggesting the combination of visual and audio elements improves student comprehension. However, the obstacle to digital LKPD internet access is still a challenge. In conclusion, multimedia increases the effectiveness of Pancasila Education learning. However, it is necessary to improve infrastructure and teacher training so that the use of multimedia is optimal and inclusive for students.